Inibitori del cotrasportatore sodio-glucosio di tipo 2 in pazienti sottoposti a trapianto renale - Aris Tsalouchos (AboutScience Srl, 2023)
Several recent randomized controlled trials (RCTs) have demonstrated the broad clinical application of sodium-glucose cotransporter-2 inhibitors (SGLT2i) in improving kidney and cardiovascular outcomes in patients with native kidney disease. In January 2023, Dapagliflozin became the first SGLT2 inhibitor approved by the Italian Medicines Agency Administration (AIFA) for the treatment of chronic kidney disease (CKD) regardless of diabetic status. However, although these agents have received considerable praise for their cardiovascular and nephroprotective effects among patients with native kidney disease, the safety and efficacy of SGLT2i in the kidney transplant setting are not well-known as safety concerns have led to the exclusion of transplant recipients from all large RCTs. This review will discuss the known mechanisms SGLT2i employ to provide their beneficial effects, the potential benefits and risks of these agents in the context of kidney transplantation, and finally, it will examine the current findings of published literature on SGLT2i use in kidney transplant recipients and propose potential directions for future research.